An approximation to the nondominated set of a multiobjective linear fractional programming problem. (2nd August 2016) - Valipour, E.; Yaghoobi, M. A.; Mashinchi, M.
Abstract : This paper presents a method for approximating the nondominated set of a multiobjective linear fractional programming (MOLFP) problem. The resulting approximation set has acceptable quality measures, and is an -approximation to the nondominated set, where is the tolerance vector and can be controlled by the decision-maker. The distance between every two resulting solutions is greater than or equal to a positive value and hence there is no redundant information. Also, for a given upper bound the method controls the cardinality of the resulting approximation set.